149k views
3 votes
What is the value of 3ab+5b-6 when a=-1 and b=3?
A.0
B.6
C.18
D.24

User Karunakar
by
6.4k points

2 Answers

1 vote

use the substitution method

3ab+5b-6

3(-1)(3)+5(3)-6

Mutiply 3(-1)(3) first

3(-1)(3)= -3*3= -9

-9+5(3)-6

then mutiply

5(3)= 15

-9+15-6

= 6-6

= 0

Answer : A. 0

User Ettanany
by
5.7k points
7 votes

Answer:

A. 0

Explanation:

3ab+5b-6

= 3(-1)(3)+5(3)-6

=3(-3)+15-6

=-9+9

=0 ( you have to subtract because they don't have the same signs)

User Hudson Taylor
by
6.1k points